Global Peatland Restoration after 30 years: where are we in this mossy world?. Issue 2 (14th September 2016) - Rochefort, Line; Andersen, Roxane
Abstract : As part of the Society of Ecological Restoration World Conference in 2015, we held a Global Peatland Restoration symposium, where we gave experts from around the world the mandate to provide an updated picture of peatland restoration in their part of the world and scan the horizon to identify challenges and opportunities to come. This special section was put together to make these valuable contributions available to all.